Puppet master 9-film collection ; Killjoy - Band, Charles; Le Mat, Paul; Scaggs, Jimmie F; Miracle, Irene; Schmoeller, David, 1947-; Frates, Robin; DeCoteau, David; Sloan, Victoria; Talbot, Robert; Sutton, Tammi; Lechago, John; Currie, Gordon, 1965-; et al. ([La Crosse, WI] : Echo Bridge Home Entertainment, 2012)
The Puppet master saga begins when psychics investigate rumors that the secret of life has been discovered by master puppeteer Andre Toulon. They quickly discover death in the form of five killer puppets, each one uniquely qualified for murder and mayhem
Killjoy series: A killer clown named Killjoy thinks murder is a laughing matter
Puppet master (88 min.) -- Puppet master 2 (85 min.) -- Puppet master 3: Toulon's Revenge (82 min.) -- Puppet master 4 (80 min.) -- Puppet master 5 (82 min.) -. Puppet master 6: Curse of the Puppet Master (80 min.) -- Puppet master 7: Retro Puppet Master (80 min) - Puppet master 8: The Legacy (72 min) - Puppet Master 9: Axis of Evil (81 min)
"Over 12 hours."
Title from container
Original story of Puppet master by Charles Band
Puppet master (2021) directed by David Schmoeller
Puppet master: Paul Le Mat, Jimmie F. Scaggs, Irene Miracle, Robin Frates
Puppet master 2: Gregory Webb, Charlie Spradling, Steve Welles, Jeff Weston, Sage Allen, Nita Talbot
Keywords: Feature films; Horror films; Puppet theater -- Drama; Clowns -- Drama; Dramas